2012
DOI: 10.1111/j.1365-2966.2012.22039.x
|View full text |Cite
|
Sign up to set email alerts
|

A tomographic study of V691 CrA (X1822−371)

Abstract: We present Doppler and modulation tomography of the low‐mass X‐ray binary V691 CrA with data obtained using the 6.5‐m Magellan Baade telescope at the Las Campanas Observatory in 2010 and 2011. The disc and hotspot are observed in Hα and He ii (λ4686) in both years. A clear image of the disc is seen in He ii (λ5411) using the 2010 data. We present the first tomography of the absorption line He i (λ5876) and detect absorption near the L1 point of the donor star. We also present the first modulation tomography of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The presence of matter in the outer region of the disc or in a region surrounding the entire system was also proposed by Harlaftis et al (1997) and Cowley et al (2003), observing that the Hα line is formed in a region not strongly eclipsed and that the Hα velocity variation is very small. These results were confirmed recently by Peris & Dil Vrtilek (2012).…”
Section: Presence Of Neutral Matter Around the Binary Systemsupporting
confidence: 81%
“…The presence of matter in the outer region of the disc or in a region surrounding the entire system was also proposed by Harlaftis et al (1997) and Cowley et al (2003), observing that the Hα line is formed in a region not strongly eclipsed and that the Hα velocity variation is very small. These results were confirmed recently by Peris & Dil Vrtilek (2012).…”
Section: Presence Of Neutral Matter Around the Binary Systemsupporting
confidence: 81%
“…Tomograms of systems both similar to V801 Ara (e.g. X1822-371 Harlaftis et al (1997); Peris & Vrtilek (2012)), and other systems in quiescence containing both neutron stars (e.g. Cen X-4, D'Avanzo et al ( 2005)) and black holes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A0620, Neilsen, Steeghs, & Vrtilek (2008)) are also consistent with an asymmetric disk. Peris & Vrtilek (2012) suggested that the combination of a disk offset from the predicted position of the neutron star and the asymmetric structure could be the indication of an eccentric disk. An eccentric disk implies disk precession.…”
Section: Discussionmentioning
confidence: 99%
“…We detect a similar bright spot, but find that it is offset from the secondary at ∆V ∼ 200 km s −1 larger Vy owing to the updated dynamical model. H α emission, identified as originating from the secondary, has been observed in other black hole and neutron star systems (e.g., Marsh et al 1994;Shahbaz et al 1999;Torres et al 2002;González Hernández & Casares 2010;Peris & Vrtilek 2012), some compatible with the Roche lobe of the secondary and some slightly offset. Although it has been commonly attributed to chromospheric activity or X-ray heating of the secondary, an unequivocal interpretation has not yet been established.…”
Section: Detection Of the Secondary Starmentioning
confidence: 99%
“…This interaction typically occurs in a small region also known as the "hotspot" and is observed in these systems both as a peak in the orbital light curve at phase ∼ 0.8 − 0.9 (where phase 0.0 is defined as the superior conjunction of the compact object) and as a bright spot at the same phase in tomograms (e.g., Krzeminski 1965;Wood et al 1986, Neilsen, Steeghs & Vrtilek 2008, Calvelo et al 2009Peris & Vrtilek 2012). Lubow & Shu (1976) were the first to suggest that some of the gaseous matter falling from the donor star onto the disc via the stream does not stop at the hotspot but flows over and under the disc.…”
Section: Introductionmentioning
confidence: 99%